2015
DOI: 10.1287/mnsc.2014.2050
|View full text |Cite
|
Sign up to set email alerts
|

Prospect Theory Explains Newsvendor Behavior: The Role of Reference Points

Abstract: Authors are encouraged to submit new papers to INFORMS journals by means of a style file template, which includes the journal title. However, use of a template does not certify that the paper has been accepted for publication in the named journal. INFORMS journal templates are for the exclusive purpose of submitting to an INFORMS journal and should not be used to distribute the papers in print or online or to submit the papers to another publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
175
3
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(188 citation statements)
references
References 16 publications
8
175
3
2
Order By: Relevance
“…These explanations include the possible inability to process information or feedback (Benzion, Cohen, Peled, & Shavit, 2008;Benzion, Cohen, & Shavit, 2010;Diehl & Sterman, 1995;Ding, Puterman, & Bisi, 2002;Perakis & Roels, 2008;Wang & Webster, 2009); national differences, cultural differences, gender differences, or differences in cognitive aptitude (Cui, Chen, Chen, Gavirneni, & Wang, 2013;De Vericourt, Jain, Bearden, & Filipowicz, 2013;Feng, Keller, & Zheng, 2011;Hoppe & Kusterer, 2011;Moritz, Hill, & Donohue, 2013); poor or limited cognition as a result of faulty reference frame or framing of information or anchoring on information (Herweg, 2013;Köszegi & Rabin, 2006;Nagarajan & Shechter, 2013;Schweitzer & Cachon, 2000); or bounded rationality (Kremer, Minner, & Van Wassenhove, 2010;Su, 2008). Recent work on the subject by Long and Nasiry (2014) and Surti and Celani (2019) shows that students, acting as newsvendors, display behavior consistent with Prospect Theory proposed by Kahneman and Tversky (1979) and together with Schweitzer and Cachon (2000) provides an improved understanding of how the newsvendor makes decisions.…”
Section: Behavioral Operations Managementmentioning
confidence: 88%
See 1 more Smart Citation
“…These explanations include the possible inability to process information or feedback (Benzion, Cohen, Peled, & Shavit, 2008;Benzion, Cohen, & Shavit, 2010;Diehl & Sterman, 1995;Ding, Puterman, & Bisi, 2002;Perakis & Roels, 2008;Wang & Webster, 2009); national differences, cultural differences, gender differences, or differences in cognitive aptitude (Cui, Chen, Chen, Gavirneni, & Wang, 2013;De Vericourt, Jain, Bearden, & Filipowicz, 2013;Feng, Keller, & Zheng, 2011;Hoppe & Kusterer, 2011;Moritz, Hill, & Donohue, 2013); poor or limited cognition as a result of faulty reference frame or framing of information or anchoring on information (Herweg, 2013;Köszegi & Rabin, 2006;Nagarajan & Shechter, 2013;Schweitzer & Cachon, 2000); or bounded rationality (Kremer, Minner, & Van Wassenhove, 2010;Su, 2008). Recent work on the subject by Long and Nasiry (2014) and Surti and Celani (2019) shows that students, acting as newsvendors, display behavior consistent with Prospect Theory proposed by Kahneman and Tversky (1979) and together with Schweitzer and Cachon (2000) provides an improved understanding of how the newsvendor makes decisions.…”
Section: Behavioral Operations Managementmentioning
confidence: 88%
“…The risk preference is likewise created in response to the information being presented. The frames and references that they create most likely reflect an individual's risk preferences or unique worldview formed through personal expectations or personal equilibrium (Köszegi & Rabin, 2006;Long & Nasiry, 2014). Static information may also create static frames of reference that may result in a person's behavior being anchored to the last piece of relevant information, resulting in non-rational behavior (Nagarajan & Shechter, 2013;Schweitzer & Cachon, 2000).…”
Section: Behavioral Operations Managementmentioning
confidence: 99%
“…Table 3 summarizes our findings. Valuation of outcome is derived from the amount of deviation from chosen reference point Newsvendor will be riskseeking (q > q * ) over negative deviation (Loss domain) and risk-averse (q < q * ) over positive deviation (Gain domain) Schweitzer and Cachon (2000), Herweg (2013), Nagarajan and Shechter (2013), Long and Nasiry (2014), Uppari and Hasija (2014), Zhao and Geng (2015), Li et al (2017) Newsvendor will be charged extra penalty for each unit of leftover inventory, so he would order less than optimal quantity (q < q * )…”
Section: Figurementioning
confidence: 99%
“…These authors showed numerically that prospect theory predicts overordering for high-profit products and underordering for low-profit products, which violates the PTC bias. Long and Nasiry [25] further stated that the prospect theory incorporating a reference point can explain PTC bias. However, many other researches do not support newsvendor's PTC bias.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the previous data in Schweitzer and Cachon [19] and Bolton and Katok [21], Lau et al [26] conducted a new experiment and showed that the PTC bias does not adequately describe the individual newsvendor decision. Zhao and Geng [27] pointed out that the model in Long and Nasiry [25] is a special case of the general prospect theory model and showed that the general prospect theory model may be powerful in predicting the preferences of decision makers in inventory management. Y. Zhao and X. Zhao [28] found that a competing environment can cause participants to significantly increase their ordering levels in the highprofit group and increase their ordering oscillations in the low-profit group.…”
Section: Introductionmentioning
confidence: 99%